Improving the Memorization of Arabic Vocabulary for Santri Pondok Pesantren Darul Qur’an Mojokerto City Through Book Design "المفردات واستخدامها الجمل " with Writing Techniques and Making Sentences|Peningkatan Hafalan Kosakata Bahasa Arab Santri Pondok Pe - Nahdiya Tul Ummah; Nurul Azizah Ria Kusrini (Mantiqu Tayr: Journal of Arabic Language, 2022)
This research has a background to determine the extent to which the use of the book "al mufrodat wa Istikhdamuha fii al Jumal" in the Darul Quran Islamic boarding school in Mojokerto City in improving the mastery of memorizing Arabic vocabulary. By utilizing this book in the learning process, it is hoped that it can provide different motivation and innovation for students in mastering memorizing Arabic vocabulary orally and in writing in an easier and more thorough manner. This research is a qualitative descriptive study. The research data was obtained by observation, where the researcher functions as an instrument to carry out continuous observations, document studies and in-depth interviews. The validity of the data is done by triangulation of sources. Meanwhile, for data analysis using interactive model analysis, namely by reducing data, presenting data, and drawing conclusions. The results of this study describe the design of the book المفرداتو استخدامها في الجمل which is very helpful for vocabulary mastery, if students are asked to write the words they have just learned when the meanings of the words are still fresh in students' minds. Students write vocabulary. The last stage of the vocabulary teaching activity is to use the new words in a perfect sentence according to the guidelines from the book orally and in writing. Exercises like this really help to strengthen vocabulary understanding and accelerate the improvement of students' vocabulary memorization.